Asymmetry in the otolith length and width of three sparid fish species collected from Iraqi waters - Abdulsamad, Saad M S; Jawad, Laith A; Al-Nusear, Azal N B; Waryani, Baradi; Rutkayová, Jitka (Marine pollution bulletin, 2020)
Bilateral asymmetry is presumed to reveal the developmental variability of the fish in polluted aquatic environments. In these habitats, high-level asymmetry develops, and these fish expend more energy to balance their growth than fish that are not under an impact. A total of 210 specimens of Acanthopagrus bifasciatus, A. latus and Sparidentex hasta were collected from the marine waters of Iraq in the northwest part of the Arabian Gulf. The asymmetry was calculated for the sagittal otolith characters of length and width. Otolith width has lower asymmetry than otolith length for the three sparid fish species investigated. An increase in the value of fluctuating asymmetry with fish length was observed. This could be a pertinent indicator of pollution in the habitat.
Keywords: otolitová membrána; Otolithic Membrane; Fishes; Animals; zvířata; Perciformes; ryby; ekosystém; Ecosystem